PERMODELAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI MENGGUNAKAN ENTERPRISE ARCHITECTURE PLANNING - RINEL, OVEL (Sainstek : Jurnal Sains dan Teknologi, 2012)
STAIN Batusangkar is oldest and require the support of information and communication technology tools in large quantities. It is necessary for procurement planning and management systems are integral and better. This study aimed to examine the overall architecture for business processes that exist in STAIN Batusangkar using enterprise modeling systems. The steps of modeling using EAP architecture is divided into two phases, namely the identification of enterprise and enterprise architecture development. Identification entreprise by defining the organization as an object to describe the vision and mission of the organization associated with the vision of information systems planning. This is done for the development of the campus architecture tailored to the business objectives. The results showed that the necessary framework of policy, strategic planning, organizational development concept of unit information and communications technology management, user management, network infrastructure and integrated information systems. Thus, we can conclude enterprise architecture modeling using enterprise information systems architecture planning can be used to assess the overall architecture of the existing business processes in STAIN Batusangkar using enterprise modeling systems. Key words: model enterprise architecture planning, STAIN Batusangkar